Acute and chronic neural stimulation via mechano-sensitive ion channels - Tay, Andy Kah Ping (Cham, Switzerland : Springer, 2018)
This book describes the tools, developed by the author, for perturbing endogenous mechano-sensitive ion channels for magneto-mechanical neuro-modulation. He explores the ways in which these tools compare against existing ones such as electricity, chemicals, optogenetics, and techniques like thermos/magneto-genetics. The author also reports on two platforms-magnetic ratcheting and magnetic microfluidics for directed evolution and high throughput culture of magnetotactic bacteria-that produce high quality magnetic nanoparticles for biomedical applications like neural stimulations. This thesis was submitted to and approved by the University of California, Los Angeles.
Publicada originalmente como la tesis del autor
Keywords: SISTEMA NERVIOSO -- ENFERMEDADES -- TRATAMIENTO; ESTIMULACIÓN NERVIOSA; NEUROFISIOLOGIA; CANALES IÓNICOS; ESTIMULACION ELECTRICA